PERAN IBU DALAM PENCEGAHAN PERILAKU SEKS BEBAS PADA REMAJA DI DESA SEI LIMBAT KECAMATAN SELESAI KAB. LANGKAT TAHUN 2025 - Suarni, Leny; Sembiring, Muhammad Nur Maghribi; Ananda, Ichfad; Nurhalila, Nurhalila (INSTITUT KESEHATAN DELI HUSADA, 2025)
Premarital sexual behavior among adolescents has become an increasingly concerning social and health issue in Indonesia, including in rural areas such as Sei Limbat Village. The rapid development of information technology and globalization exposes adolescents to various influences that shape their attitudes and behaviors related to sexuality. This condition highlights the crucial role of mothers in guiding and protecting their children from risky behaviors. Mothers, through emotional closeness and open communication, play a vital role in providing moral guidance and reproductive health education. However, cultural taboos, limited knowledge, and lack of time often hinder mothers from fulfilling this role effectively. Strengthening parental awareness, promoting open dialogue within families, and involving schools, communities, and local governments are essential strategies to prevent risky sexual behavior among adolescents.